Microsurgical and Endoscopic Anatomy of the Extended Retrosigmoid Inframeatal Infratemporal Approach. Issue 2 (March 2015) - Colasanti, Roberto; Tailor, Al-Rahim A.; Gorjian, Mehrnoush; Zhang, Jun; Ammirati, Mario
Abstract : BACKGROUND: Different and often complex routes are available to deal with jugular foramen tumors with extracranial extension. OBJECTIVE: To describe a novel extension of the retrosigmoid approach useful to expose the extracranial area abutting the posterior fossa skull base. METHODS: A navigation-guided, endoscope-assisted retrosigmoid inframeatal approach was performed on 6 cadaveric heads in the semisitting position, displaying an area from the internal acoustic meatus to the lower cranial nerves and exposing the intrapetrous internal carotid artery. We then continued removing the temporal bone located between the sigmoid sinus and the hearing apparatus, reaching the infratemporal area just lateral to the jugular fossa. This drilling, which we refer to as posterolateral inframeatal drilling, has not previously been described. Drilling of the horizontal segment of the occipital squama allowed good visualization of the uppermost cervical internal carotid artery, internal jugular vein, and lower extracranial cranial nerves. RESULTS: We were able to provide excellent exposure of the inframeatal area and of the posterior infratemporal fossa from different operative angles, preserving the neurovascular structures and the labyrinth in all specimens. The intradural operative window on the extracranial compartment was limited by the venous sinuses and the hearing apparatus and presented a mean width of 8.52 mm. Sigmoid sinus transection led to better visualization of the lateral half of the jugular foramen and of the uppermost cervical internal carotid artery. CONCLUSION: The navigation-guided endoscope-assisted extended retrosigmoid inframeatal infratemporal approach provides an efficient and versatile route for resection of jugular foramen tumors with extracranial extension. ABBREVIATIONS: ES, endolymphatic sac ICA, internal carotid artery IJV, internal jugular vein